BAM, a project of the century
The Baikal-Amur Magistral (BAM) is a broad gauge railway line in Russia, traversing Eastern Siberia and the Russian Far East. The BAM was built as a strategic alternative route to the Trans-Siberian Railway, especially along the vulnerable sections close to the border with China. Built over permafrost and due to the severe terrain, weather, length and cost Brezhnev described BAM as "the construction project of the century."